Another Proof of An Uncountability Real Numbers Set - M. Ofie,; E. Herawati, (Journal of Research in Mathematics Trends and Technology, 2020)
The diagonalization argument is one way that researchers use to prove the set of real numbers is uncountable. In the present paper, we prove the same thing by using the supremum property in the set of real numbers.